2002
DOI: 10.1161/01.cir.0000019739.66514.1e
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the 5′-Flanking Region of Human Glutamate-Cysteine Ligase Modifier Subunit Gene Is Associated With Myocardial Infarction

Abstract: Background-Human glutamate-cysteine ligase (GCL) is a rate-limiting enzyme for the synthesis of glutathione that plays a crucial role in antioxidant defense mechanisms in most mammalian cells, including vascular cells. Oxidants transcriptionally upregulate GCL genes for glutathione synthesis, providing a protective mechanism against oxidative stress-induced cellular dysfunction. This study examined the hypothesis that variation in the GCL genes may be associated with coronary artery disease in which oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
3
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 28 publications
1
116
3
1
Order By: Relevance
“…1,5-7 However, we have previously shown that the Ϫ588T polymorphism suppresses the increase in GCLM gene expression in response to oxidative stress and that this polymorphism is associated with low plasma GSH concentration. 8 Therefore, the Ϫ588T polymorphism may weaken the intracellular production of GSH in response to oxidative stress, leading to an increase in the susceptibility to impairment of NO-mediated endothelial vasomotor function. In addition, endothelium-derived NO has various antiatherothrombogenetic properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,5-7 However, we have previously shown that the Ϫ588T polymorphism suppresses the increase in GCLM gene expression in response to oxidative stress and that this polymorphism is associated with low plasma GSH concentration. 8 Therefore, the Ϫ588T polymorphism may weaken the intracellular production of GSH in response to oxidative stress, leading to an increase in the susceptibility to impairment of NO-mediated endothelial vasomotor function. In addition, endothelium-derived NO has various antiatherothrombogenetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping was performed by a polymerase chain reaction-based method of restriction fragment length polymorphism with forward (5Ј-CTCAAGGGCAAAGACTCA-3Ј) and reverse (5Ј-CCGCCTGGTGAGGTAGACAC-3Ј) primers, as described previously. 8 …”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…The T allele has shown lower promoter activity compared to the C allele in vitro in human endothelial cells (Koide et al 2003). The 5'-flanking region of GCLM contains a polymorphism (-588C/T) in which the T allele has shown lower promoter activity compared to C allele when exposed to oxidants (Nakamura et al 2002). Nakamura et al (2002) also showed that the plasma GSH levels were significantly lower in CT and TT genotypes than in CC genotype.…”
Section: Polymorphisms Analyzedmentioning
confidence: 98%